Clinical outcomes following primary percutaneous coronary intervention for ST-elevation myocardial infarction according to sex and race. Issue 3 (1st April 2019) - Krishnamurthy, Arvindra; Keeble, Claire; Burton-Wood, Natalie; Somers, Kathryn; Anderson, Michelle; Harland, Charlotte; Baxter, Paul D; McLenachan, James M; Blaxill, Jonathan M; Blackman, Daniel J; Malkin, Christopher J; Wheatcroft, Stephen B; et al.
Abstract: Background: Female sex and South Asian race have been associated with poor clinical outcomes following primary percutaneous coronary intervention (PPCI) for ST-segment elevation myocardial infarction (STEMI) but remain understudied in large real-world series. We therefore investigated the association of sex and race with clinical outcomes following PPCI. Methods: We conducted a prospective study of all patients undergoing PPCI for STEMI between January 2009 and December 2011 at a large UK cardiac centre. Clinical characteristics and outcomes were compared according to sex and race using Chi-square test, independent samples Student's t -test and Mann–Whitney U -test. Primary and secondary outcomes were 12-month major adverse cardiovascular events (MACEs) – defined as all-cause mortality, myocardial infarction and unplanned revascularization, analysed using Cox proportional hazard models adjusting for cardiovascular risk factors. Results: Three thousand and forty-nine patients were included. Women ( n =826) were older than men ( n =2223) (median age 69 vs . 60 years, p <0.01). Mortality (hazard ratio 1.48 (1.15–1.90)) and MACE (hazard ratio 1.40 (1.14–1.72)) were higher in women in univariable analysis. However, there were no significant sex-differences in mortality or MACE after age-stratification alone. Multivariable analysis also showed no significant differences in outcomes between sexes. South Asians ( n =297) were younger but had a higher prevalence of most risk factors than White patients ( n =2570). Mortality and MACE did not differ significantly between South Asian and White patients in univariable or multivariable analysis. Conclusion: MACE and mortality was not greater in women, or in South Asian patients following PPCI after adjustment for cardiovascular risk factors including age, which was most strongly associated with both outcomes.